Laboratory Engagement and Conceptual Mastery in Chemistry - John Lloyd P. Alarcon; James L. Paglinawan (Scientia Publica Media, 2026)
Optimizing science pedagogy within the K–12 STEM curriculum requires identifying the practical drivers of academic achievement, which remains a vital educational priority. This study examines the relationship between laboratory engagement and conceptual mastery in chemistry among Science, Technology, Engineering, and Mathematics students. Using a descriptive-correlational design, the research surveyed 347 students from selected private institutions in Valencia City, Bukidnon, during the 2024–2025 and 2025–2026 school years. Data were collected through two researcher-made, expert-validated, 30-item questionnaires—the Chemistry Laboratory Engagement Questionnaire and the Conceptual Mastery Questionnaire—both of which demonstrated high internal consistency. These data were subsequently analyzed using descriptive statistics and Pearson correlation analysis. Descriptive results indicate that students maintain a moderate level of laboratory engagement overall (3.91). Within this domain, collaborative learning received the highest rating (4.18), followed by technology integration (3.82) and hands-on experimentation (3.73). Similarly, students’ conceptual mastery in chemistry was rated as very satisfactory overall (3.81); while problem-solving skills yielded the highest performance (4.07), the lower scores for conceptual change (3.68) and knowledge application (3.67) highlight specific opportunities for targeted instructional improvement. Pearson correlation analysis demonstrated a significant positive linear relationship between laboratory engagement and conceptual mastery (r = .445, p < 0.05), leading to the rejection of the null hypothesis. The study concludes that active and effective laboratory participation is crucial for promoting deeper conceptual understanding and academic performance in chemistry. It recommends that educational institutions prioritize robust laboratory programs emphasizing hands-on learning and structured collaborative practices.